2016
DOI: 10.1089/vbz.2015.1897
|View full text |Cite
|
Sign up to set email alerts
|

Low Seroprevalence Indicates Vulnerability of Eastern and Central Sudan to Infection with Chikungunya Virus

Abstract: Outbreaks of infections with chikungunya virus (CHIKV) have previously been reported from Sudan but the prevalence in the general population is unknown. We investigated the seroprevalence of CHIKV infection in 379 serum samples from patients with fever in the outpatient clinics of three hospitals in eastern and central Sudan. The seroprevalence was 1.8%, indicating that CHIKV infections are rare in these parts of Sudan. As the vector Aedes aegypti is endemic in this area, the population is at risk for a CHIKV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 7 publications
(7 reference statements)
2
17
0
Order By: Relevance
“…ONNV, SINV, and SFV) or travel-acquired infections were observed or could not be excluded in some studies from Djibouti [27], Iran [28], Kuwait [29, 30], and Pakistan [26]. Viral neutralization testing was performed in a total of five studies from Djibouti [31], Iraq [32, 33], and Sudan [3234]. Among acute febrile illness studies, the prevalence of laboratory-supported CHIKV infection was also highest in Sudan, with anti-CHIKV antibody prevalence by HI or ELISA ranging from 1.8% to 30%.…”
Section: Resultsmentioning
confidence: 99%
“…ONNV, SINV, and SFV) or travel-acquired infections were observed or could not be excluded in some studies from Djibouti [27], Iran [28], Kuwait [29, 30], and Pakistan [26]. Viral neutralization testing was performed in a total of five studies from Djibouti [31], Iraq [32, 33], and Sudan [3234]. Among acute febrile illness studies, the prevalence of laboratory-supported CHIKV infection was also highest in Sudan, with anti-CHIKV antibody prevalence by HI or ELISA ranging from 1.8% to 30%.…”
Section: Resultsmentioning
confidence: 99%
“…An epidemiological survey in East Sudan using quantitative reverse transcription polymerase chain reaction (qRT-PCR) showed that 24% of pregnant women were infected with CHIKV and the infections were associated with preterm delivery [44]. A wider study across the country reported a relatively low seroprevalence of CHIKV in East and Central Sudan (1.8%) with 100% dengue virus seropositivity [61]. A large-scale outbreak of chikungunya was ongoing in East Sudan between May 2018 and March 2019, with more than 47,000 laboratory-confirmed cases [62,63].…”
Section: Chikungunya Virusmentioning
confidence: 99%
“…Understandably, during epidemics of febrile illnesses, it is challenging to distinguish arboviral diseases from malaria and other infections due to the lack of laboratory capacity for proper diagnostics [5,6]. Despite the frequent reports of chikungunya from different parts of Sudan, there were no entomological studies investigating the vectors of the disease [61].…”
Section: Chikungunya Virusmentioning
confidence: 99%
“…The infection is divided into acute and chronic phases. In 2016, several CHIKV outbreaks have been reported from different locations in Sudan, although the prevalence in the general population is unknown [9,21,22].…”
Section: Introductionmentioning
confidence: 99%